Disseminated Intravascular Coagulation - Lorens, Jane Olivia; Kurniawan, Andree (Medicinus, 2017)
Disseminated Intravascular Coagulation (DIC) is an acquired pathological syndrome, featured by a hypercoagulable state, bleeding symptoms, and multiple organ failure. Based by these very distinct features, DIC is classified into four types namely Bleeding type, Organ failure type, Massive bleeding type, and Asymptomatic type. Diagnosing DIC is a challenge to the health practitioner, considering that DIC is a multifactorial syndrome, which always is a complication of some underlying diseases. To diagnose DIC, it is necessary to do a comprehensive evaluation of clinical symptoms and laboratory results. The necessary laboratory results include platelets count, fibrin degradation products (FDPs), fibrinogen, and PT-aPTT.